Does whole-body vibration training have a positive effect on balance and walking function in patients with stroke? A meta-analysis - Yin, Yikun; Wang, Jialin; Yu, Zhengze; Zhou, Lina; Liu, Xiaoman; Cai, Hejia; Sun, Junzhi (Frontiers in Human Neuroscience, 2023)
Objective After a stroke, patients usually suffer from dysfunction, such as decreased balance ability, and abnormal walking function. Whole-body vibration training can promote muscle contraction, stimulate the proprioceptive system, enhance the muscle strength of low limbs and improve motor control ability. The study aims to evaluate the effectiveness of whole-body vibration training on the balance and walking function of patients with stroke. Methods PubMed, CNKI, VIP, CBM, EBSCO, Embase and Web of Science were searched. According to the inclusion and exclusion criteria, randomized controlled trials on the effectiveness of whole-body vibration training on the balance and walking function of patients with stroke were collected. The search time ranged from the date of database construction to November 2022. The included trials were evaluated by the Cochrane risk-of-bias tool. The meta-analysis was performed using two software packages, consisting of RevMan 5.4 and Stata 12.2. If the results included in the literature were continuous variables, use the mean difference (MD) and 95% confidence interval (CI) for statistics. Results 1) A total of 22 randomized controlled trials (RCTs) with a total of 1089 patients were included. 2) The results of meta-analysis showed that: compared with the controls, step length (MD=6.12,95%CI [5.63,6.62], p<0.001), step speed(MD=0.14,95%CI[0.09,0.20],p<0.001), cadence(MD=9.03,95%CI[2.23,15.83],p=0.009), stride length (MD=6.74,95%CI[-3.47,10.01],p<0.001), Berg Balance Scale (BBS) (MD=4.08,95%CI[2.39,5.76],p<0.001), Timed Up-and-Go test (TUGT) (MD=-2.88,95%CI[-4.94,0.81],p=0.006), 10-meter Walk Test (10MWT) (MD=-2.69,95%CI [-3.35, -2.03], p<0.001), functional ambulation category scale (FAC) (MD=0.78,95%CI[0.65,0.91],p<0.001), Fugl-Meyer motor assessment of lower extremity (FMA-LE) (MD=4.10,95%CI[2.01,6.20],p=0.0001). 3) The results of subgroup analysis showed that, compared with other vibration frequencies, at 20-30Hz frequency, WBV training had an obvious improvement effect only in TUGT. 4) The safety analysis showed that WBV training may be safe. Conclusion Whole-body vibration training has a positive effect on the balance and walking function of patients with stroke. Thus, whole-body vibration training is a safe treatment method to improve the motor dysfunction of patients with stroke.